Exploring the challenges and implications of designing, developing and implementing accessible e-government services - Abdurahman, Saleem (Department of Information Systems, 2023)
E-Government is perceived to be a vehicle for transforming how governments deliver public services and interact with each other and with their citizens as well as businesses. Governments present their services via their online websites. It is therefore paramount that e-Government services are accessible and well-designed to allow all those who use the services the ability to use them. Yet, accessibility of e-Government websites continues to remain a challenge to people with disability (PWDs) worldwide, and more so in low to middle income countries where the majority of PWDs reside. This dissertation examines the challenges e-Government designers and developers face when designing and implementing accessible e-Government services with the key purpose of understanding how these challenges affect their current practices of designing and implementing accessible e-Government services. The study employed qualitative techniques, specifically qualitative semi-structured interviews to collect primary data from government employees working as developers, designers, business analysts, and the management team. For triangulation purposes, secondary data from South African government websites was collected to identify and understand how government is incorporating accessibility into its policies and legislatures. The data was analysed using a thematic analysis. The findings present six challenges: legacy and bespoke systems, human and financial resources, stakeholder awareness of accessibility, monitoring of accessibility, collaboration in prioritising of accessibility and management support. All of which influence the design and implementation of accessible e-Government services. Furthermore, these findings explain how these challenges affect the current practices of designing and implementing accessible eGovernment services. Identified common practices include championing accessibility, adoption of an omni channel approach as well as digital learning and awareness, development of inhouse guidelines and best practices as well as support for developing assistive technologies. The study discusses the implications of these findings for future studies.